The Heteromorphic Approach to Adjunctions: Theory and History - David Ellerman (Mathematics, 2024)
Mallios and Zafiris emphasize that adjoint functors, or adjunctions, are not only “ubiquitous” in category theory but also characterize the naturality of their approach to physical geometry. Hence, in this paper, the history and theory of adjoint functors is investigated. Where do adjoint functors come from mathematically, and how did the concept develop historically?